Preferences of inflammatory arthritis patients for biological disease-modifying antirheumatic drugs in the first 100 days of the COVID-19 pandemic - Kalyoncu, Umut; Pehlivan, Yavuz; Akar, Servet; Kasifoglu, Timucin; Kimyon, Gezmis; Karadag, Omer; Kiraz, Sedat (Tubitak Scientific & Technological Research Council Turkey, 2021)
Background/aim: To evaluate treatment adherence and predictors of drug discontinuation among patients with inflammatory arthritis receiving bDMARDs within the first 100 days after the announcement of the COVID-19 pandemic. Materials and methods: A total of 1871 patients recorded in TReasure registry for whom advanced therapy was prescribed for rheumatoid arthritis (RA) or spondyloarthritis (SpA) within the 3 months (6-9 months for rituximab) before the declaration of COVID-19 pandemic were evaluated, and 1394 (74.5%) responded to the phone survey. Patients' data regarding demographic, clinical characteristics and disease activity before the pandemic were recorded. The patients were inquired about the diagnosis of COVID-19, the rate of continuation on bDMARDs, the reasons for treatment discontinuation, if any, and the current general disease activity (visual analog scale, [VAS]). Results: A total of 1394 patients (493 RA [47.3% on anti-TNF] patients and 901 SpA [90.0% on anti-TNF] patients) were included in the study. Overall, 2.8% of the patients had symptoms suggesting COVID-19, and 2 (0.15%) patients had PCR-confirmed COVID-19. Overall, 18.1% of all patients (13.8% of the RA and 20.5% of the SpA; p = 0.003) discontinued their bDMARDs. In the SpA group, the patients who discontinued bDMARDs were younger (40 [21-73] vs. 44 years [20-79]; p = 0.005) and had higher general disease activity; however, no difference was relevant for RA patients. Conclusion: Although the COVID-19 was quite uncommon in the first 100 days of the pandemic, nearly one-fifth of the patients discontinued bDMARDs within this period. The long-term effects of the pandemic should be monitored.
Keywords: COVID-19; biologic DMARDs; rheumatoid arthritis; spondyloarthritis